DEVELOPING AN ENVIRONMENT-BASED SCIENCE TEXTBOOK: ITS RELEVANCE AS A REINFORCEMENT FOR THE CHARACTER OF ENVIRONMENT CARE - Muhammad Nuruddin; Ratih Asmarani; Claudya Zahrani Susilo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to develop an environment-based science textbook and to examine its relevance in reinforcing students’ environmental care character. This study aimed to contribute to the development of primary education, particularly in teaching the basic concepts of science in the PGSD Study Program. The development referred to Thiagarajan’s 4-D model (1974). Data were obtained from material analysis and validated by experts. A trial was then conducted with PGSD students at Hasyim Asy’ari University to produce a high-quality environment-based science textbook. Based on descriptive analysis, the textbook development process was carried out in accordance with the prescribed stages. Inferential statistics were analyzed using SPSS 26.0, including the F-test and t-test. The F-test assuming two similar variances yielded a score of 3.671 with p = 0.068, indicating no significant difference between the variances (p > 0.05). The t-test assuming equal variances yielded a score of 4.522 with p = 0.000, showing a significant difference in learning outcomes between students using the developed textbook and those using regular textbooks (p < 0.05). In conclusion, the developed environment-based science textbook was feasible and significantly improved students’ learning outcomes.